A Stock Market Prediction Module Based on Ann&Swarm Intelligence - sayed, Yaser El (Journal of Global Economy, Business and Finance, 2024)
The forecasting of prices movements in financial market on daily or certain time period basis is one of the prime concerns and challenging for both researchers and investors. The characteristics of ripples of stock prices movements reflect unpredictable, non- stationary, non-linear, noisy, and chaotic tendency. A stock market is a public market for securities where the organized issuance and trading of company stocks take place either through exchange or over the counter in physical or electronic forms. It is now a day commonly known that huge amounts of capital are traded through stock markets across the world. However, the accurate prediction of stock market movements is highly challenging as well as being an important issue for investors, and it has received much attention from practitioners and experts in financial time series research. This research work develop the module which can be useful in the predication of Indian Stock exchange with the help of ANN (Artificial Neural Network and Swarm intelligence techniques.